Adverse effects of sympathomimetic drugs in a group of adolescents - Jerí, F. Raúl (1971)
Clinical observations of 35 youths who used hallucinogenic drugs for two to four years are mostly present . The proportion of males was three times compared to women , almost all households were from well integrated and belonged to a higher socio- economic level or medium . The drugs used were marijuana , LSD , barbiturates , mescaline , afetamina , methaqualone and alcohol, in various combinations . All of these young people showed signs of psychological disturbance , personality disorders generally , before starting the use of hallucinogens . In this series it has been shown that sympathomimetic drugs (marijuana , LSD, mescaline and amphetamine ) can trigger severe acute psychotic symptoms , sub - acute and chronic . It is necessary that the health authorities establish comprehensive programs for prevention and treatment of addictions in youth, to control the pandemic currently extiéndese the main cities of Peru .